EDUTAINMENT AS A NEW TREND IN ENGLISH LANGUAGE TEACHING - Ibrohimova Marhabo Ulugbek kizi; Shukurova Shohsanam Kakhramon kizi (Galaxy International Interdisciplinary Research Journal, 2022)
The article is devoted to the issue of successful assimilation of lexical and grammatical material by students in foreign language lessons within the framework of a meta-subject approach. Since it is the formation of meta-subject results that is one of the main requirements of the State of Educational Standard, the authors of the article pay special attention to the concept of "edutainment" as a meta-subject aspect in the development of students’ language competence and their motivation to learn foreign languages